Analysis of the Application of Blended Learning Models in Physics Learning During the COVID-19 Pandemic - Kirana Aureola Arzak (International Journal of Current Educational Research, 2022)
This research was carried out to analyze physics learning using a blended learning model during the COVID-19 pandemic in Indonesia. The method used in this study is the literature study method. A literature study is a type of research used in collecting data and information by collecting and reviewing various references. This study examined as many as 30 journals and articles both nationally and internationally that are valid and accountable. The journals and articles used are published in 2018-2022. Researchers collect data and proceed to the stage of concluding the results of qualitative research. Based on the results of studies and analyses that have been carried out, it can be concluded that: (1) The application of the blended learning model to physics learning is declared valid, practical, and effective as an alternative to learning during the COVID-19 pandemic, (2) The blended learning model can improve students' critical thinking skills and creative thinking abilities, (3) Students tend to ignore academic and social aspects.